The constrained court : law, politics, and the decisions justices make - Bailey, Michael A., 1969-; Maltzman, Forrest, 1963- (Princeton : Princeton University Press, 2017)
'The Constrained Court' combines new theoretical insights and extensive data analysis to show that law and politics together shape the behaviour of justices on the Supreme Court.
Previously issued in print: 2011.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 5, 2017).
Keywords: United States. -- Supreme Court; Political questions and judicial power -- United States; Law; United States of America, USA; Laws of specific jurisdictions & specific areas of law; Legal systems: courts & procedure; Legal systems: judicial powers